DESCRIPTION OF THE COURSE OF MULTIPLE DRUG RESISTANT TUBERCULOSIS AND EFFICACY OF ITS TREATMENT IN THE PATIENTS WITH CONFOUNDING FACTORS - I. S. Gelberg; E. N. Аlekso; S. B. Volf; S. N. Demidik; Yu. A. Sheyfer; A. M. Masilevich; Ya. Z. Аrtsukevich (Туберкулез и болезни лёгких)
.